2022-LBA-1663-ESGO Should delayed debulking/cytoreductive surgery be offered to all advanced ovarian/fallopian tubal cancer patients that did not have surgery?. (27th October 2022) - Souza, Natasha D; Myriokefalitaki, Eva; Floreskou, Alvin Michael; Sap, Katelijn; Slade, Richard J; Datta, Meghna; Winter-Roach, Brett; Smith, Michael; Hasan, Jurjees
Abstract : Introduction: Primary and Interval Debulking/Cytoreductive Surgery (PDS and IDS) are standard of care for surgical management of advanced Ovarian/Fallopian Tubal Cancer. There has been very little regarding outcomes of Delayed Debulking Surgery (DDS) performed upon completion of adjuvant chemotherapy. Aim to evaluate survival outcomes following DDS and compare cytoreductive outcomes, post-operative morbidity and survival outcomes in women who underwent PDS, IDS, DDS. Methods: Prospective data collection and retrospective review of all cases that underwent DDS in our centre from 1/7/2014 to 31/12/2020We are looking into disease free and overall survival in relation to PCI score pre and post surgical excision, Chemotherapy response (CRS) and use of maintenance treatment in all three groups PDS, IDS and DDS Results: DDS is not inferior to PDS and IDS as long as compete cytoreduction achieved. OS not statistically different in between the three groups. Conclusions: Delayed debulking surgery should be offered to women who have missed the opportunity for various clinical and personal reasons to undergo surgery in the primary or interval setting. We recommend that all cases that did not have surgery to be considered for surgery at completion of their chemotherapy by MDT.